Prospective Mathematics Teachers’ Beliefs and Representations - Sadrack Luden Pagiling; Irmawaty Natsir; Markus Palobo; Dian Mayasari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2022)
Beliefs have been identified as an affect on the psychology of mathematics education. Additionally, representations play a paramount role in mathematics teaching and learning. However, few studies have examined prospective teachers' beliefs and their relationship to representations in problem-solving. The purpose of this study is to examine prospective mathematics teachers' beliefs and representations in solving word problems review from gender differences. This study involves 103 college students from the mathematics education department at a public university in Merauke Regency. The data were gathered using a questionnaire, a test, and in-depth interviews. A questionnaire was utilized to elicit the belief of prospective teachers. A test and interview were conducted to evoke data about participants' representations when solving word problems. The male student was found to be capable of arriving at a solution employing multiple representations. Due to the inaccurate representation constructed, the female student was unable to find the correct solution. This work implies that lecturers should heed prospective teachers' beliefs and generate representations of the focal point of classroom learning practice.